Does Innovation Mediate Good Firm Performance? - Gilberto M. Llanto; Fatima del Prado (Philippine Institute for Development Studies (PIDS), 2015)
Private firms invest in physical capital and human resource but they are also advised to invest in innovations to be more productive and profitable. Innovations refer to the development, deployment, and economic utilization of new products, processes, and services. It is important for firms to know whether investment in innovations is investment well-spent. Our empirical results provided an affirmative response to the question raised in this paper: "Does innovation mediate good firm performance?" Product and process innovations lead to increase in sales and profits and improve labor productivity. The paper also showed that firm size, age, and foreign equity are important factors leading firms to innovate.
Keywords: 330; innovation; Philippines; process innovation; product innovation; firm performance; small and medium enterprises (SMEs)